FACTORS OF SOIL EROSION IN THE CÓRREGO RICO WATERSHED, SÃO PAULO, BRAZIL - Costa, Beatriz de Oliveira; Oliveira, Gildriano Soares de; Pissara, Teresa Cristina Tarlé; Campos, Sérgio; Werner, Armin; Santos, Jorge Pereira; Vanzela, Luiz Sérgio (IRRIGA, 2018)
FACTORS OF SOIL EROSION IN THE CÓRREGO RICO WATERSHED, SÃO PAULO, BRAZIL BEATRIZ DE OLIVEIRA COSTA1;GILDRIANO SOARES DE OLIVEIRA2; TERESA CRISTINA TARLÉ PISSARRA2; SERGIO CAMPOS1; ARMIN WERNER3; JORGE PEREIRA SANTOS4 E LUIZ SERGIO VANZELA5 1Pós-Doutoranda; Professor Doutor, Departamento de Engenharia Agrícola, Faculdade de Ciências Agronômicas FCA UNESP, Botucatu, São Paulo, Brasil, beatriz.oliveira.costa@hotmail.com; seca@fca.unesp.br 2Mestre em Agronomia; Professora Doutora, Departamento de Engenharia Agrícola, Faculdade de Ciências Agrárias e Veterinárias FCAV UENSP, Jaboticabal, São Paulo, Brasil, gilsoaresoliveira@yahoo.com.br, teresap@fcav.unesp.br 3Pesquisador Doutor, Lincoln Agritech, New Zealand, Armin.werner@lvl.co.nz 4Geógrafo, AMS Kepler, Rio de Janeiro, Brasil, procdigital@gmail.com 5Professor Doutor, Universidade Camilo Castelo Branco – UNICASTELO, Fernandópolis, São Paulo, Brasil, lsvanzela@yahoo.com.br 1 ABSTRACT This study aimed to estimate soil losses in 1984 and 2011, in Córrego Rico Watershed (CRW) using the Universal Soil Loss Equation (USLE) and propose alternatives that might mitigate the degradation in this area. In erodibility (K) the highest value was in Alfisol Red Yellow and the lowest in Oxisol. For factor S the largest area is in embossed wavy with 33,100.20 ha (57.06%) and slope from 8.1 to 20%. In the factors Vegetation and Soil Management (C) and Conservation Practices (P) it was observed that in these years there were considerable changes such as the reduction of pasture and fruit trees areas and increased areas of cane sugar. A positive balance was increased vegetation cover of 1,993.95 ha in 1984 to 4,895.25 ha in 2011. The highest soil loss in the class occurred in an area of 26.44% in 1984 and 2011 in an area of 30.22%. The integrated use of USLE and GIS proved to be an effective technique in the spatial representation of soil loss in Córrego Rico watershed to identify areas most vulnerable to erosion process and in spatial-temporal variability. Keywords: USLE, land use, map algebra COSTA, B. O.; OLIVEIRA, G. S.; PISSARRA, T. C. T.; CAMPOS, S.; WERNER, A.; SANTOS, J. P.; LUIZ SERGIO VANZELA, L. S. FATORES DE EROSÃO DO SOLO NA BACIA HIDROGRÁFICA DO CÓRREGO RICO, SÃO PAULO, BRASIL 2 RESUMO Este trabalho teve por objetivo estimar as perdas de solo nos anos de 1984 e 2011, na bacia hidrográfica do Córrego Rico (BHCR), utilizando a Equação Universal de Perda de Solo (EUPS) e propor alternativas que possam mitigar a degradação nesta área. Na erodibilidade (K) o valor mais elevado foi no Argilossolo Vermelho-Amarelo e o menor no Latossolo Vermelho. Para o fator S a maior área está em relevo ondulado com 33.100,20 ha (57,06 %) e Declividade entre 8,1 a 20 %. Nos fatores Cobertura Vegetal e Manejo do Solo (C) e Práticas Conservacionistas (P) nota-se que nestes anos houve grandes mudanças tais como a diminuição das áreas de pastagem e frutíferas e o aumento das áreas de cana-de-açúcar. Um saldo positivo foi o aumento da cobertura vegetal de 1.993,95 ha em 1984 para 4.895,25 ha em 2011. A maior perda de solo na classe, ocorreu numa área de 26,44 % em 1984 e 2011 em uma área de 30,22 %. O uso integrado de EUPS e SIG mostrou ser uma técnica eficaz na representação espacial das perdas de solo na bacia hidrográfica do Córrego Rico para identificação das áreas mais vulneráveis ao processo erosivo e na variabilidade espaço‐temporal. Palavras–chave: EUPS, uso do solo, álgebra de mapas